The Role of Distress Tolerance in the Use of Specific Emotion Regulation Strategies. (May 2016) - Jeffries, Emily R.; McLeish, Alison C.; Kraemer, Kristen M.; Avallone, Kimberly M.; Fleming, John B.
The present study evaluated the role of distress tolerance (DT), defined as the ability to tolerate negative emotional states, in the use of four specific emotion regulation strategies (suppression, avoidance, rumination, and reappraisal). Undergraduate psychology students ( N = 431, 71.7% female; M age = 19.80 years, SD = 3.71) completed self-report measures online for course credit. It was hypothesized that, after controlling for the effects of anxiety sensitivity and negative affectivity, DT would be negatively associated with suppression, avoidance, and rumination, and positively associated with reappraisal. Consistent with prediction, low DT significantly predicted greater use of suppression, avoidance, and rumination. However, contrary to prediction, DT did not significantly predict reappraisal. These results suggest that individuals who are unable to withstand negative emotions are more likely to use maladaptive regulation strategies.